A palm-size μNMR relaxometer using a digital microfluidic device and a semiconductor transceiver for chemical/biological diagnosis1. Issue 15 (7th August 2015) - Lei, Ka-Meng; Mak, Pui-In; Law, Man-Kay; Martins, Rui P.
<x xml:space="preserve">Abstract</x> We describe the first electronic-automated multi-step multi-sample palm-size μNMR relaxometer exhibiting four key functionalities: (1) high-sensitivity μNMR screening; (2) inside-magnet sample management; (3) real-time multi-droplet positioning; and (4) multiplexed μNMR.